Use of Direct LAMP Screening of Broiler Fecal Samples for Campylobacter jejuni and Campylobacter coli in the Positive Flock Identification Strategy - Sabike, Islam I.; Uemura, Ryoko; Kirino, Yumi; Mekata, Hirohisa; Sekiguchi, Satoshi; Okabayashi, Tamaki; Goto, Yoshitaka; Yamazaki, Wataru (Frontiers in Microbiology, 2016)
Rapid identification of Campylobacter-positive flocks before slaughter, following freezing and heat treatment for the Campylobacter-positive carcasses at the slaughterhouses is an effective control strategy against foodborne campylobacteriosis. We evaluated a loop-mediated isothermal amplification (LAMP) assay for the direct screening of naturally contaminated chicken cloacal swabs for Campylobacter jejuni/Campylobacter coli to compare this assay with conventional quantitative culture methods. In a comparison study of 165 broilers, the LAMP assay showed 82.8% (48/58 by conventional culture) sensitivity, 100% (107/107) specificity, 100% (48/48) positive predictive value (PPV), and 91.5% (107/117) negative predictive value (NPV). In a comparison of 55 flocks, LAMP showed 90.5% (19/21) sensitivity, 100% (34/34) specificity, 100% (19/19) PPV, and 94.4% (34/36) NPV. In the cumulative total of 28 farm-level comparisons, LAMP showed 100% (12/12) sensitivity, 100% (16/16) specificity, 100% (12/12) PPV, and 100% (16/16) NPV. The LAMP assay required less than 90 min from the arrival of the fecal samples to final results in the laboratory. This suggests that the LAMP assay will facilitate the identification of C. jejuni/C. coli-positive broiler flocks at the farm level or in slaughterhouses before slaughtering, which would make it an effective tool in preventing the spread of Campylobacter contamination.